ANDRAGOGICAL APPROACHES IN FOREIGN COUNTRIES: THEORETICAL ASPECTS AND MODELS - Yusupov U. K. (Bright Mind Publishing, 2025)
The article analyzes the theoretical aspects of andragogical approaches and their various models applied in the educational practice of Germany. It highlights the scientific foundations of andragogy, the specific characteristics of adult education, and the principles of independence, motivation, and experience-based learning in the educational process. The article also presents the advantages of andragogical models in enhancing educational effectiveness, their adaptability to the national vocational education system, and practical recommendations for their implementation.
Keywords: Andragogy, andragogical approach, adult education, foreign experience, andragogical models, educational effectiveness, innovative approach, vocational education.